TRANSFORMATION OF DRAMA APPRECIATION LEARNING THROUGH INTERACTIVE MULTIMEDIA BASED ON ARTICULATE STORYLINE FOR UNPARI STUDENTS - Agung Nugroho; Inda Puspita Sari; Dian Ramadan Lazuardi (Linggau Journal Science Education (LJSE), 2025)
This research aims to develop interactive multimedia based on Articulate Storyline for Drama Appreciation learning for students of the Indonesian Language and Literature Study Program at UNPARI (Indonesian University). The research method used was Research and Development (R&D) using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of validation experts, lecturers, and students of the Indonesian Language and Literature Study Program at UNPARI. Data were collected through observation, interviews, questionnaires, and tests, using validation sheets, response questionnaires, and evaluation questions. The results showed that the developed interactive multimedia product achieved a validity level with an average score of 0.89, which is categorized as very valid. The results of the practicality test, based on lecturer and student assessments, showed a percentage of 96.15%, categorized as very practical. Furthermore, the effectiveness test, analyzed using N-Gain, showed an average score of 0.72, which is categorized as high. This indicates an increase in students' understanding of the Drama Appreciation material after using this learning media. Based on the research results, it can be concluded that interactive multimedia based on Articulate Storyline in Drama Appreciation learning for UNPARI students has proven valid, practical, and effective, making it suitable for use as a learning medium to improve the quality of student learning processes and outcomes.